2005
DOI: 10.1002/pssc.200461139
|View full text |Cite
|
Sign up to set email alerts
|

Electronic, structural and optical properties of hydrogenated silicon nanocrystals: the role of the excited states

Abstract: PACS 61.46.+w, 71.15.Mb, 81.07.Bc In this paper we report on a first-principle calculation of the electronic and structural properties of hydrogenated silicon nanocrystals both in the ground-and in an excited-state configuration. The presence of an electron-hole pair created under excitation is taken into account and its effects on both the electronic spectrum and the cluster geometry are pointed out. The interpretation of the results is done within a four-level model, which also allows the explanation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 8 publications
(13 reference statements)
5
25
0
Order By: Relevance
“…We first consider only dopants substituting for the atom at the center of the nanocrystals. Donor-doped nanocrystals with hydride-terminated surface have electron binding energies between 2.2 and 2.5 eV (Table ), in agreement with previous results. ,, Note that this is about half the I UD (0/+) – I UD (−/0) gap, and 2 orders of magnitude higher than the activation energies for the same group V dopants in bulk silicon. Similar to bulk silicon, As has a slightly higher E b than P and Sb.…”
Section: Ionization Energy and Electron Affinitysupporting
confidence: 90%
See 1 more Smart Citation
“…We first consider only dopants substituting for the atom at the center of the nanocrystals. Donor-doped nanocrystals with hydride-terminated surface have electron binding energies between 2.2 and 2.5 eV (Table ), in agreement with previous results. ,, Note that this is about half the I UD (0/+) – I UD (−/0) gap, and 2 orders of magnitude higher than the activation energies for the same group V dopants in bulk silicon. Similar to bulk silicon, As has a slightly higher E b than P and Sb.…”
Section: Ionization Energy and Electron Affinitysupporting
confidence: 90%
“…The fraction of dopant atoms at the surface of nanocrystals has been related to the energetics of the substitutional dopant, in particular the dependence of the formation energy on its distance to the surface. , Additionally, it was found that the formation energy of substitutional P and B is higher the smaller the nanocrystal diameter. , In the basis of these findings, a self-purification mechanism whereby impurities are expelled was proposed . Another possibility is that the distribution of dopant atoms is controlled by the kinetics of adsorption of impurities on the nanocrystal surface during growth …”
Section: Introductionmentioning
confidence: 99%
“…Any progress therefore has to rely upon bold simplifications, especially with regard to the size and geometry of the model. Hence, a common approach is to limit the problem to a particular region of interest, either by (i) using finite boundary conditions, , or by (ii) adopting a periodic slab-, wire-, or particle-in-a-box approach, hoping that within such a limited region the model is still able to adequately capture the electronic local density of states. In such supercell calculations, it is also common to impose a sufficiently large vacuum space to separate the structure replicas, and by this way to mitigate unwanted periodicity effects .…”
Section: Methodsmentioning
confidence: 99%
“…First-principles modeling studies of doped Si NCs have shown that dopant atoms are energetically preferenced toward the outer surface region; 40,41 however, experimental evidence has been mixed. Oxidation-etching experiments of doped Si NCs from low-pressure plasmas indicated a preference for boron to be found in the core of the Si NCs with phosphorus found in the near-surface region.…”
mentioning
confidence: 99%